POTENSI PESANTREN DALAM PENGEMBANGAN EKONOMI SYARIAH - Marlina Marlina (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
In the social system of Muslim society in Indonesia, pesantrens play a vital role in forming the ideal Muslim society order. Pesantrens and their sources also become the agent of social change because of their inclusive characteristics.The more rapid shariah economy, either as the economy system or as economics, makes sure the role of pesantrens because of the potencies that they have. The potencies that we can get from pesantrens to develop shariah economy are: (1) pesantrens as agents of social changing in the field of shariah economy; (2) pesantrens as shariah business laboratoriums, and (3) pesantrens as the centre to learn syariah economy.